DEVELOPMENT OF MATHEMATICS LEARNING DEVICES BASED ON PROBLEM BASED LEARNING MODELS ON THE MATERIAL OF POLYHEDRON TO FACILITATE MATHEMATICS PROBLEM-SOLVING ABILITY FOR SMP/MTS STUDENTS - Shania Uthami Putri; Atma Murni (Jurnal Prinsip Pendidikan Matematika, 2021)
Abstract. This research to produce a product in the form mathematical learning devices using Problem Based Learning model on the material of Constructing Flat Side Spaces to facilitate students Mathematics Problem Solvibg Ability. The development model used is the ADDIE model namely Analysis, Design, Development, and Evaluation. The research instrument used is validity instrument and practicality. The instrument of validity is in the form of a validation sheet to assess the validity of the learning tools, namely the Syllabus, Lesson Plans, and LKPD. The practical instrument in the form of student response questionnaires to assess the usability and ease of use of LKPD. Learning Tools that have been developed will be validated by three validators and revised according to the validator's suggestions. Next, a small group trial was conducted with six students. The results of the average validation score for the Syllabus 3.84, RPP 3.75, and LKPD 3,64, so that the learning tools are categorized as very valid. The result of the average percentage of practicality of LKPD is 91.15% with very practical category. Based on the results of data analysis, it was concluded that this study produced a product in the form of a mathematical learning device based on the Problem Based Learning model on the material of Constructing Flat Sided Space that was valid for Syllabus, RPP, and LKPD and practical for LKPD.